The International Workingmen's Association, Gramsci and the labour-education relationship: reflections for contemporary educational policy : (PerCursos, 2024)
Facing contemporary neoliberal counter-reforms that deepen social and educational inequalities, the article aims to revisit conceptions and proposals for education and its relationship with labour, historically present in workers' movements, and to analyse to which measure they can contribute today to actions of resistance and the organisation of educational policies of the subaltern classes in the struggles for hegemony. The discussion is carried out through theoretical-bibliographical research, which aims to disseminate ideas from the socialist approach to education. We point out that the proposals for an emancipatory education have a long historical trajectory, that the spaces of active participation of the 19th-century movements, in particular the International Workingmen's Association and the Paris Commune, were the means of circulation of pedagogical ideas for the integral education of the working class. We take up the formulations of Karl Marx, Paul Robin, Antonio Gramsci, Anatoli Lounatcharski and Nadezhda Krupskaya on labour as an educational principle. We emphasise Gramsci's contributions considering the relevance of his thinking to the contemporary educational debate, concerning the link between the school and the process of disputing hegemony and apprehending reality. In this sense, we set out the challenges for the intransigent defence of public, secular, democratic and socially-referenced quality education in human, integral and scientific formation, which provides the children of the subaltern classes the possibility of being leaders and building their own future.
Keywords: contemporary education; socialist movements international workingmen's association; Antonio Gramsci; the labour-education relationship